2012
DOI: 10.1103/physrevlett.109.246803
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic-Field-Induced Localization in 2D Topological Insulators

Abstract: Localization of the helical edge states in quantum spin Hall insulators requires breaking time reversal invariance. In experiments this is naturally implemented by applying a weak magnetic field B. We propse a model based on scattering theory that describes the localization of helical edge states due to coupling to random magnetic fluxes. We find that the localization length is proportional to B −2 when B is small, and saturates to a constant when B is sufficiently large. We estimate especially the localizatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 27 publications
4
61
0
Order By: Relevance
“…Each level then crosses E F at a different time. Due to spin-orbit coupling, the particles have a finite probability of flipping their spin in the emission process 30,31 , which corresponds to a change in the propagation direction. The emitted particles are thus in a superposition of left-and rightmovers, leading to entanglement as discussed below.…”
Section: Fig 1 (Color Online)mentioning
confidence: 99%
See 1 more Smart Citation
“…Each level then crosses E F at a different time. Due to spin-orbit coupling, the particles have a finite probability of flipping their spin in the emission process 30,31 , which corresponds to a change in the propagation direction. The emitted particles are thus in a superposition of left-and rightmovers, leading to entanglement as discussed below.…”
Section: Fig 1 (Color Online)mentioning
confidence: 99%
“…The frozen (in time) scattering matrix of the SES can be calculated as in Ref. 31 and reads (up to a global phase)…”
Section: Fig 1 (Color Online)mentioning
confidence: 99%
“…66,67,69,78,92 Terms related to bulk inversion asymmetry, 8,22 Rashba spin-orbit coupling 13,76 and/or magnetic fields 19,21 can also be included here. The envelope function is given by…”
Section: Hyperfine Interactions For a Nanostructure In A Hgte Quanmentioning
confidence: 99%
“…[13][14][15][16][17][18] The effect of external magnetic fields have also been considered. 6,8,[19][20][21][22][23][24] The TI state in HgTe QWs was predicted by Bernevig, Hughes, and Zhang (BHZ) 25 by using a simplified k · p model containing states with S-and P -like symmetries, respectively. They found that beyond a critical thickness of the HgTe QW, the TI state would appear as confirmed experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect of perpendicular magnetic field in these conditions is much smaller and manifests itself at B z ∼ 1 T, similar to the case of in-plane field. To describe the effect of the perpendicular field, several theoretical approaches * Electronic address: raichev@isp.kiev.ua have been proposed, including numerical simulation of transport based on a 2D disordered site model [8], as well as analytical consideration of the possibility of enhanced backscattering due to edge spectrum nonlinearity induced by the magnetic field [9] and of interference effects at a disordered edge allowing for loops of the helical edge states [10]. The approach of Ref.…”
Section: Introductionmentioning
confidence: 99%